Anthropometric Marker Contribution Assessment for Celiac Disease and Gluten-Free Diet in Portuguese Children - Soares, Patrícia; Lemos, Piedade Sande; Pires, Ana Maria; Sousa, Ana Cláudia Cavaco de (Issues and Development in Health Research Vol. 3, 2021)
Celiac disease (CD) is an autoimmune disease characterised by chronic food sensitivity to gluten, as well as diarrhoea and weight loss as typical symptoms. The epidemiology and phenotype of CD are constantly changing, whereas the symptoms exhibited by children with CD are variable and influenced by age. The present study aimed to examine anthropometric marker progressions in 61 Portuguese children with celiac disease at the time of diagnosis and at the time of the study, correlating these differences with gluten-free product intake. Data from 61 celiac disease patients (59.0 percent females) who had been on a gluten-free diet for5.0 ± 4.6 years were analysed. A statistical t-test examination of pBMI at diagnosis and over the study period demonstrated a statistically significant positive increase for both girls and boys (p = 0.008). The discrepancies between ingested and suggested values were measured, revealing that overall energy consumption and carbohydrate consumption had increased. Most children's nutritional status can be restored by following a gluten-free diet; nevertheless, nutritional counselling appears to be necessary to avoid nutrient imbalances and future health problems.